Influence of employments physical exercises on age-dependent changes and rates of senescence of organism for women 30-50 years - Sorokina S.A (Kharkov National Pedagogical University, 2010)
The special program of positive influence is developed on the general state of organism of women. The analysis of the special literature is conducted. In an experiment 26 women took part in age 30-50 years. Practical recommendations are developed in relation to employments by physical exercises. The use at health run and walking, respiratory exercises, exercises under musical accompaniment, engaged in yoga, is offered. Positive changes are fixed in the indexes of the functional state of the cardiovascular system and nervous system.